Dynamic disorders: narratives of eating disorders and the father-daughter relationship - Mouton, Ashton, author; Broadfoot, Kirsten, advisor; Aoki, Eric, committee member; Canetto, Silvia, committee member (Colorado State University. Libraries, 2011)
Eating disorders affect women all over the world, particularly adolescents, at a rate which has grown in the last several decades. As obesity becomes one of the most battled health risks, those seriously underweight are ignored, praised, and/or forgotten, and as the fear of obesity grows, so does the incidence and prevalence of eating disorders. Previous research on eating disorders has focused on the family system and/or the mother-daughter dyad for their etiological significance, but relatively little attention has been given to the father's place in the family system or the father-daughter dyad in this context. Using Bronfenbrenner's (1979) ecological model as a lens, this thesis expands the literature of eating disorders by asking questions about the father-daughter relationship and the father's role(s) in the development, maintenance, and recovery of their daughter's eating disorder experiences. Narrative interviews, which record daughters' perceived experiences of the father-daughter relationship in the context of their eating disorders, were collected from women who self-identify as having an eating disorder. Analysis of the daughters' narrative accounts reveals six themes that define the father-daughter relationship and daughters' experiences of their eating disorders. Throughout the narratives, daughters communicatively construct their relationships with their fathers through the dialectical tensions of closeness/distance and openness/closedness. Interestingly, daughters do not communicatively construct their relationships with their fathers based on interactions about food, weight, or appearance but rather around issues of quality interactions, support, and closeness, as daughters construct the father-daughter relationship as an evolving emotional experience. Eating disorders, then, are perceived as relational artifacts of the father-daughter relationship, marking certain relational turning points. Within the narratives, fathers potentially enable the development of the eating disorder through actions and inactions nonrelated to daughters' food intake, appearance, or behavior and potentially further enable the performance of the eating disorder through their silence and passive reactions to their daughters' disorders. However, fathers have the potential to aid in the recovery process with care, support, and expressed closeness, and when fathers do actively participate in their daughters' recovery, the relationship and the recovery process can both benefit from their active participation. These findings highlight the need for further research on fathers (and other father-figures) in this context. Future studies should examine and compare narratives of both fathers and daughters in this context to gain a more complete picture of the father-daughter relationship experience. In addition, future studies should inquire about the family's influence on eating disorders but also the eating disorder's influence on family interactions. Finally, future research should conduct studies with relational dialectics and relational turning points as their main focus in families with eating disorders.
Keywords: communication; narrative; fathers; father-daughter relationship; eating disorders